Migrant remittances and socio-economic status of recipient households in the DRC: Case of Congolese migrants in the Western Cape in South Africa - Nzonde, Patient (Graduate School of Business (GSB), 2018)
More than two decades of internal fighting and political unrest have seen millions of Congolese people leave their home country in search of a better future for themselves and their families in other parts of the world. This migratory movement exposed most of them to the significance of remittances as a means to support the loved ones left behind. Remittances from abroad play a key role in enhancing the standard of living of households in the Democratic Republic of Congo (DRC). The study therefore analyzed remitting behaviours of migrants based in the Western Cape province of South Africa and the impact of their remittances on recipients’ livelihood in the Democratic Republic of Congo. This study made use of primary and secondary data collected from various sources, then applied qualitative methods for analyzing both the remittance senders’ behaviour and the impact on recipient households. After a critical analysis, the study found that remittances increase the income of recipients, help alleviate poverty, improve recipients’ ability to access basic services such as health and education, and contribute to employment creation by providing capital for microenterprises and community based projects. The study also found that migrants based in the Western Cape would rather use informal channels instead of formal channels due to high costs and compliance requirements. One contribution of this study is the finding that current policies in relation with the remittance industry in South Africa and in Congo can definitely be improved in order to increase remittances inflows both ways, and thus meaningfully impact both countries’ economies.